The importance of physical activity in elderly people with diabetes: integrative review (Research, Society and Development, 2022)
Introduction: Diabetes mellitus (DM) is a chronic pandemic disease that affects approximately 422 million people worldwide, and its prevalence is expected to double in the next 20 years, estimated at 22-33% in the elderly. Aware that PA brings many health benefits, doctors strongly recommend that elderly people with a medical condition, diabetes in this case, practice this action in their daily lives so that they have a healthier quality of life. Methodology: This is an integrative literature review, where the main journal databases used for active article searches were: Scielo, PubMed, Google Scholar, Who. Results and discussions: T2DM is defined as a carbohydrate-related metabolic disease common among older adults with diabetes, who have rapid loss of muscle mass, strength and neurological function, and poorer performance in functional tests, making it an acutely increased risk of diabetes. physical disability and frailty in this population. Physical activity is recognized as the cornerstone of the management of DM2 for improving blood sugar and cardiovascular risk factors, aiding in weight loss, possibly playing a role in the prevention of chronic complications. Conclusion: A The research starts from the need to emphasize the magnitude of PA, given that this practice should be directed not only to young people, but mainly to the elderly, and in this case to diabetics, thus improving their physical fitness, which among several factors influence and enhance the improvement of the well-being of this target audience.